Hol(e)y texts; hol(e)y lives : on the Psalms and spirituality, with particular attention to Thessalnia DePrince, Thomas Merton and Beat Weber - described, compared and evaluated - Lombaard, Christo J. S. (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2015)
Continuing from the author's previously published research track on Biblical Spirituality, in this paper three different approaches to reading the Psalms in relation to faith experience are taken into review. First, the theoretical framework for the analyses to be conducted, is presented. Then, three specific works that focus on the Psalms and faith experience, but in quite different ways, are discussed: DePrince's generally esoteric approach, Merton's more spiritual approach and Weber's exegetically-grounded approach. Each of these approaches are, in turn, described and analysed, after which comparisons are drawn to indicate similarities and differences. Based on the initially presented theoretical framework, an evaluation is offered of each of the three approaches. In conclusion, the evaluative difficulty of the interaction between Bible text and reader's faith is touched upon.
free